1986
DOI: 10.1002/pssa.2210940112
|View full text |Cite
|
Sign up to set email alerts
|

Heat Capacities of TlInS2 and TlInSe2 Crystals at Low Temperatures

Abstract: The heat capacities of ternary TlInS2 and TlInSe2 layer crystals are studied a t low temperatures. The dependence of the characteristic temperatures θD on the temperature of these crystals is plotted. It is shown that the low‐temperature part of the heat capacities of TlInS2 and TlInSe2 depends on the temperature according to a linear law in the region of 8 to 30 K. A number of anomalies are revealed in the Cp(T) heat capacity behaviour of TlInSe2 crystals in the range from 170 to 215 K. The results obtained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 1 publication
1
17
0
Order By: Relevance
“…It was suggested [6,7] that these transitions are driven by the presence of an incommensurate phase within the T 1 -T 2 tempera ture region. There was a report [8] of a low tempera ture (4.2-300 K) study of the TlInSe 2 heat capacity, but no anomalies were found in the C p = f(T) curve. In studies of the dielectric response of the TlInSe 2 crystal [9], a PT was shown to exist, which could be assigned to formation of an incommensurate phase at T i = 210 K and its transition with decreasing temperature into the commensurate one, with the PT splitting into two modes at T c1 = 200 K and T c2 = 196.8 K. The dif…”
Section: Introductionmentioning
confidence: 92%
“…It was suggested [6,7] that these transitions are driven by the presence of an incommensurate phase within the T 1 -T 2 tempera ture region. There was a report [8] of a low tempera ture (4.2-300 K) study of the TlInSe 2 heat capacity, but no anomalies were found in the C p = f(T) curve. In studies of the dielectric response of the TlInSe 2 crystal [9], a PT was shown to exist, which could be assigned to formation of an incommensurate phase at T i = 210 K and its transition with decreasing temperature into the commensurate one, with the PT splitting into two modes at T c1 = 200 K and T c2 = 196.8 K. The dif…”
Section: Introductionmentioning
confidence: 92%
“…found on the dependence c p = f(T) in the temperature range of 4.2-300 K when studying the specific heat of TlGaTe 2 crystal [6]. The authors [7] found a phase transition at Т 1 ~ 98.5 K in TlGaTe 2 when studying the specific heat of this crystal.…”
Section: Introductionmentioning
confidence: 96%
“…Both crystals undergo a phase transition from the paraelectric phase to the incommensurate phase ͑T i ϳ 120 K in TlGaSe 2 ͒ and then to the ferroelectric phase ͑T c ϳ 110 K in TlGaSe 2 ͒. [3][4][5][6][7] Early investigations of thermal expansion in TlGaSe 2 , TlInS 2 , and TlGaS 2 were made in Refs. 8 and 9.…”
Section: Introductionmentioning
confidence: 99%